Pengujian Material Absorpsi Bunyi dari Serbuk Kayu Menggunakan Tabung Impedansi Dua Mikrofon - Felix Marcellino Henrikus; Adita Sutresno; Ferdy Semuel Rondonuwu (Jurnal Teori dan Aplikasi Fisika, 2025)
A study was conducted to test sound-absorbing materials made from teak wood waste by comparing the effect of the number of holes in the material on its absorption coefficient. This research utilized a two-microphone impedance tube with a length of 1.82 m and a diameter of 0.07 m, where the sound propagation speed was determined by measuring the fundamental frequency based on the open organ pipe principle. By determining this propagation speed, the resonance frequency of the tube was used as the basis for measuring the absorption coefficient, and the microphones were positioned at the nodes and antinodes of the standing wave at each frequency to obtain the standing wave ratio. The results indicated that non-perforated and perforated materials exhibited different absorption patterns, with non-perforated material being more effective in absorbing sound at low frequencies, while perforated material showed a broader absorption effectiveness at medium to high frequencies. Thus, the design of sound-absorbing materials with holes offers a more flexible and adaptive solution for noise control in various environmental conditions, making it a potential innovation in acoustic technology and the development of environmentally friendly materials. Keywords: sound absorption coefficient, acoustic panels, impedance tube, standing waves.